ChemInform Abstract: Microwave‐Assisted Synthesis of 4‐Substituted 2‐Methylthiopyrimidines. Issue 45 (23rd October 2014) - Thomann, Andreas; Boerger, Carsten; Empting, Martin; Hartmann, Rolf W.
Abstract Pyrrol and indole do not react with (I) under the investigated conditions.